Assessment of Preoperative Functional Status Prior to Major Head and Neck Surgery: A Pilot Study. (22nd June 2021) - Miller, Ashley L.; Holcomb, Andrew J.; Parikh, Anuraag S.; Richards, Julianne M.; Rathi, Vinay K.; Goldfarb, Jeremy W.; Remenschneider, Aaron K.; Bergmark, Regan W.; Annino, Donald J.; Goguen, Laura A.; Rettig, Eleni M.; Deschler, Daniel G.; et al.
Abstract : Objective: To demonstrate feasibility of a recently developed preoperative assessment tool, the Vulnerable Elders Surgical Pathways and Outcomes Analysis (VESPA), to characterize the baseline functional status of patients undergoing major head and neck surgery and to examine the relationship between preoperative functional status and postoperative outcomes. Study Design: Case series with planned data collection. Setting: Two tertiary care academic hospitals. Methods: The VESPA was administered prospectively in the preoperative setting. Data on patient demographics, ablative and reconstructive procedures, and outcomes including total length of stay, discharge disposition, delay in discharge, or complex discharge planning (delay or change in disposition) were collected via retrospective chart review. VESPA scores were calculated and risk categories were used to estimate risk of adverse postoperative outcomes using multivariate logistic regression for categorical outcomes and linear regression for continuous variables. Results: Fifty‐eight patients met study inclusion criteria. The mean (SD) age was 66.4 (11.9) years, and 58.4% of patients were male. Nearly one‐fourth described preoperative difficulty in either a basic or instrumental activity of daily living, and 17% were classified as low functional status (ie, high risk) according to the VESPA. Low functional status did not independently predict length of stay but was associated with delayed discharge (odds ratio [OR], 5.0; 95% CI, 1.2‐21.3; P =. 030) and complex discharge planning (OR, 5.7; 95% CI, 1.34‐24.2; P =. 018). Conclusion: The VESPA can identify major head and neck surgical patients with low preoperative functional status who may be at risk for delayed or complex discharge planning. These patients may benefit from enhanced preoperative counseling and more comprehensive discharge preparation.